2022
DOI: 10.1021/acs.jpcc.2c02087
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Doping Modulates 2D Intrinsic Ferromagnetic Mn2Ge2Te6 Monolayer, High Curie Temperature, Large Magnetic Crystal Anisotropy

Abstract: Mn2Ge2Te6 shows intrinsic ferromagnetic (FM) order, with a Curie temperature (T c) of 316 K. The FM order origins from superexchange interaction between Mn and Te atoms. Mn2Ge2Te6 is half-metal (HM), and spin-β electron is a semiconductor with a gap of 1.462 eV. Mn2Ge2Te6 tends to show in-plane anisotropy (IPA), with a magnetic anisotropy energy (MAE) of −13.2 meV/f.u. Mn2Ge2Te6 shows good dynamical and thermal stability. Moreover, Mn2Ge2Te6 presents good ferromagnetic and half-metallic stability under charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…111-AA-2 and 111-AA-SI-2 have a D 3 point group, while 111-AB-2 and 111-AB-SI-2 have a C 3 point group. As a result, the energy difference Δ E 0 is independent of the in-plane azimuthal angle ϕ, ,, and the energies with EA along the [100] and [010] directions are the same . In consequence, K 4 equals 0, as shown in Figures S11b,c and a,b.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…111-AA-2 and 111-AA-SI-2 have a D 3 point group, while 111-AB-2 and 111-AB-SI-2 have a C 3 point group. As a result, the energy difference Δ E 0 is independent of the in-plane azimuthal angle ϕ, ,, and the energies with EA along the [100] and [010] directions are the same . In consequence, K 4 equals 0, as shown in Figures S11b,c and a,b.…”
Section: Resultsmentioning
confidence: 84%
“…Compared with k 2 and k 3 , k 1 is much larger, which is similar to CGT, as shown in Figure S11b. According to Figure b, MAE could be calculated by the following equation M A E = E false[ 100 false] E false[ 001 false] The corresponding MAEs of CGT with 111-AA-2 and 111-AB-2 stackings are 1.80 and 1.91 meV/f.u., as shown in Figure S11c, respectively. The positive MAE implies EA is along the out-of-plane direction, that is, parallel to the c -axis, which indicates perpendicular magnetic anisotropy (PMA), as shown in Figure S11a .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Curie temperature of Cr 2 NOF was higher than that of some recently proposed 2D magnetic materials, such as CrI 3 , 47 FeX 3 (X = F, Cl, and I) 48 Mn 2 Ge 2 Te 6 , 49 but slightly lower than that of FeBr 3 . 50 In addition, based on molecular dynamics simulation, it was found that the magnetic state of Cr 2 NOF can exist at room temperature. Here, in order to illustrate the applications of the Janus MXene, we used a Cr 2 NOF/2DH (graphene, BN, MoS 2 , GaN) bilayer as an example to discuss the effect of the contact with different 2DHs on the electronic properties.…”
Section: Introductionmentioning
confidence: 99%